EZH2 is required for parathyroid and thymic development through differentiation of the third pharyngeal pouch endoderm - Cinzia Caprio; Gabriella Lania; Marchesa Bilio; Rosa Ferrentino; Li Chen; Antonio Baldini (The Company of Biologists, 2021)
The Ezh2 gene encodes a histone methyltransferase of the polycomb repressive complex 2 that methylates histone H3 lysine 27. In this study, we investigated whether EZH2 has a role in the development of the pharyngeal apparatus and whether it regulates the expression of the Tbx1 gene, which encodes a key transcription factor required in pharyngeal development. To these ends, we performed genetic in vivo experiments with mouse embryos and used mouse embryonic stem cell (ESC)-based protocols to probe endoderm and cardiogenic mesoderm differentiation. Results showed that EZH2 occupies the Tbx1 gene locus in mouse embryos, and that suppression of EZH2 was associated with reduced expression of Tbx1 in differentiated mouse ESCs. Conditional deletion of Ezh2 in the Tbx1 expression domain, which includes the pharyngeal endoderm, did not cause cardiac defects but revealed that the gene has an important role in the morphogenesis of the third pharyngeal pouch (PP). We found that in conditionally deleted embryos the third PP was hypoplastic, had reduced expression of Tbx1, lacked the expression of Gcm2, a gene that marks the parathyroid domain, but expressed FoxN1, a gene marking the thymic domain. Consistently, the parathyroids did not develop, and the thymus was hypoplastic. Thus, Ezh2 is required for parathyroid and thymic development, probably through a function in the pouch endoderm. This discovery also provides a novel interpretational key for the finding of Ezh2 activating mutations in hyperparathyroidism and parathyroid cancer.